Significant Earth’s responses of the 2022 Tonga eruption across Taiwan from multiple sensor observations - Huang, Bor-Shouh; Ku, Chin-Shang; Lin, Chin-Jen; Hsu, Ya-Ju; Liu, Tien-Chi; Liu, Jann-Yenq; Chen, Yen-Ling Eileen; Chen, Da-Yi; Huang, Treng-Shi; Jiang, Juen-Shi (Frontiers in Earth Science, 2024)
On January 15, 2022, a massive underwater volcano erupted in the Tonga region, releasing a significant amount of volcanic ash and gases into the atmosphere. The United States Geological Survey (USGS) estimated the seismic source to have a surface wave magnitude (Ms) of 5.8. This eruption was clearly observed from space, and the resulting atmospheric shockwave swept across the Pacific Ocean. Reports from various locations worldwide indicated rapid fluctuations in air pressure following this event. Taiwan, situated in the western Pacific, approximately 8,500 kilometers away from the eruption source, observed significant changes of the Earth responses. During this volcanic eruption, not only the rapid air pressure changes but several significant changes in Earth's physical parameters were commonly observed in Taiwan. The Tonga eruption is a unique event and comprehensive observations provide an opportunity to explore and explain the mechanisms behind this extreme event. Comprehensive observations provide an opportunity to explore and explain the mechanisms behind this extreme event. In this study, data from ground surface air pressure gauges, coastal tide gauges, underwater pressure gauges, infrasound sensors, digital microphones, and seismometers were collected. These data were individually analyzed to identify its origin and attempt to jointly explain their interactions. The results of this study first present the detailed propagation characteristics of air pressure waves in the Taiwan region and verify the occurrence of a specific tsunami phenomenon caused by the atmospheric disturbance from the Tonga eruption. It follows a distinct mechanism, explaining its arrival time and wave height distribution around Taiwan, which is different from conventional tsunamis of tectonic origins, which are formed by rapid changes in water caused by earthquakes or underwater landslides.